Analytical reactivity of 13 commercially available rapid influenza diagnostic tests with H3N2v and recently circulating influenza viruses. Issue 4 (3rd April 2014) - Bose, Michael E.; Sasman, Amy; Mei, Hong; McCaul, Kate C.; Kramp, William J.; Chen, Li‐Mei; Shively, Roxanne; Williams, Tracie L.; Beck, Eric T.; Henrickson, Kelly J.
<x xml:space="preserve">Abstract</x> Objectives Rapid influenza diagnostic tests (RIDTs) used widely in clinical practice are simple to use and provide results within 15 minutes; however, reported performance is variable, which causes concern when novel or variant viruses emerge. This study's goal was to assess the analytical reactivity of 13 RIDTs with recently circulating seasonal and H3N2v influenza viruses, using three different viral measures. Design Virus stocks were characterized by infectious dose (ID50) and nucleoprotein (NP) concentration, diluted at half‐log dilutions, and tested with each RIDT and real‐time RT‐PCR. Results Strong correlation was observed between NP concentration and RIDT reactivity; however, only weak correlation was seen with ID50 or Ct values. Only four RIDTs detected viral NP at the lowest dilution for all influenza A viruses (IAV). Influenza A viruses not detected by more than one RIDT had lower NP levels. Of the 13 RIDTs, 9 had no significant differences in reactivity across IAV when compared to NP levels. Conclusions Previous reports of RIDT performance typically compare reactivity based on ID50 titers, which in this study correlated only weakly with proportional amounts of viral NP in prepared virus samples. In the context of the strong correlation of RIDT reactivity with NP concentration, H3N2v was found to be as reactive as seasonal circulating IAV. While these findings may not reflect clinical performance of these RIDTs, measuring NP concentration can be useful in the future to assess comparable reactivity of available RIDTs, or to assess reactivity with newly evolving or emerging viruses.